Influenza and pneumococcal vaccination: do older people know if they have been vaccinated? - Alice Laurence; Peter Lewis; Colleen Gately; Andrew Dixon (Elsevier, 2016)
Abstract Objective: To estimate influenza and pneumococcal immunisation rates by self‐report and validate this with immunisation providers. Method: A random population telephone survey. This was followed by contacting immunisation providers of those reporting having an influenza vaccination (2009 or 2010 only) and/or pneumococcal vaccination to confirm vaccination or not. Results: A total of 680 people aged 65 and older responded to the telephone survey. Seventy‐five per cent of respondents self‐reported influenza vaccination in 2010 and 26% self‐reported having ever had the pneumococcal vaccination. Following up with immunisation providers, we found recall for influenza vaccination was confirmed in 96% of cases. For the pneumococcal vaccination, recall for vaccination was confirmed in 87% of cases. People saying they were not vaccinated for pneumococcal were subsequently confirmed as vaccinated in 77% of cases. Conclusions: In this study, self‐reported influenza vaccination was reliable. The term 'pneumococcal vaccination or Pneumovax' was poorly recognised by our telephone survey respondents as evident by the low rate of self‐reported pneumococcal vaccination compared to a much higher rate of pneumococcal vaccinations recorded by GPs. Implications: While pneumococcal vaccination is an accurate term, researchers should be aware of the terminology used in general practice and the community when designing their survey.